2004
DOI: 10.1038/labinvest.3700144
|View full text |Cite
|
Sign up to set email alerts
|

Role of differential and cell type-specific expression of cell cycle regulatory proteins in mediating progressive glomerular injury in human IgA nephropathy

Abstract: The activities of cell cycle regulatory proteins have been reported to be associated with the development of pathological lesions in glomerulonephritis. To assess the cellular mechanisms underlying the mesangial cell proliferation and glomerulosclerosis in progressive human IgA nephropathy (IgAN), we examined the expression of E2F1, Rb, c-Myc, proliferating cell nuclear antigen (PCNA), cyclins (D1, E and A), cyclindependent kinase 2 (CDK2) and CDK inhibitors (p21 waf1 , p27 kip1 , 57 kip2 and p16 ink4a ) by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 43 publications
2
26
1
1
Order By: Relevance
“…This observation is in contrast to the findings of Shankland et al [28], who noted decreased p27 expression during the mesangioproliferative phase of anti-thymocyte plasma-induced glomerulonephritis in rats. Additionally, in renal biopsy specimens of patients with IgA nephropathy, a decrease of glomerular p27 expression was found in proliferative and sclerosing lesions [29]. Upregulation of glomerular p27 expression leads to cell hypertrophy [30], whereas proliferation is associated with a decrease in p27 levels [31].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in contrast to the findings of Shankland et al [28], who noted decreased p27 expression during the mesangioproliferative phase of anti-thymocyte plasma-induced glomerulonephritis in rats. Additionally, in renal biopsy specimens of patients with IgA nephropathy, a decrease of glomerular p27 expression was found in proliferative and sclerosing lesions [29]. Upregulation of glomerular p27 expression leads to cell hypertrophy [30], whereas proliferation is associated with a decrease in p27 levels [31].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of disagreement in the scoring, the process was repeated and the final score was For semi-quantitative analysis, glomerular endothelial and mesangial cells were counted together. In addition, a seven-point scoring system was employed for the evaluation of podocyte positive signals (NF-κB, p65, p50, TNF-α and IL-1β) in glomeruli that took both intensity and extent into account [34,36]. Podocytes were primarily identified by architectural features revealed on light microscopy by mild PAS counterstaining.…”
Section: Semi-quantitative Histological Analysismentioning
confidence: 99%
“…KLF15 binds to the GC-rich region of the promoter for transcription factor E2F1 [11], which regulate the expression of cell cycle proteins [31]. The initiation and amplification of mesangial cell proliferation have been linked to glomerular sclerosis and the downregulation of mesangial cell E2F1 expression in human IgA nephropathy [32]. In this study, siRNA target to E2F1 was cotransfected with siKLF15 into RMCs; the results indicated that increase of cell proliferation induced by siKLF15 can be eliminated partly by siE2F1.…”
Section: Discussionmentioning
confidence: 97%